Ellipsis in the vP domain in Mandarin and Xhosa - Ma, Xiujie (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2017)
This thesis provides a unified analysis of ellipsis in the vP domain in two typologically different languages, Mandarin and Xhosa from a generative perspective. It starts with the V-stranding Verb Phrase Ellipsis (VPE) assumption and shows that Mandarin and Xhosa do not have V-stranding VPE. The evidence for this is that in both languages, the constituents that remain in vP obligatorily are not allowed to be deleted, whereas the ones that can/must move out of vP can be deleted. The deleted constituents display the characteristics of PF-deletion, i.e. they have an internal syntactic structure. Based on the parallel between movement and ellipsis of the vP-internal constituents, I propose the Ellipsis EPP Hypothesis to account for ellipsis in the vP domain. The Hypothesis predicts that there is an Ellipsis Phrase at the left periphery of vP. The EP bears an Ellipsis-EPP (EEPP) feature, which must be satisfied. Maximal phrases in the c-command domain of EP are all potential candidates for satisfying the EEPP feature by moving to [Spec, EP]. However, only the phrases that are allowed to move out of vP can move to [Spec, EP] as EP is located above vP. Moreover, the movement to [Spec, EP] is subject to the syntactic and semantic restrictions in structure-building in that ellipsis is one operation in the course of structure-building and the derivation will continue after ellipsis takes place. The EEPP feature renders an XP in the specifier phonetically empty and syntactically frozen; therefore, a constituent will be deleted as soon as it moves to [Spec, EP]. The Hypothesis is schematically represented below. The Ellipsis EPP Hypothesis adequately accounts for the ellipsis of various vP-internal constituents - NPs, DPs, infinitive complements and CP complements - in both Mandarin and Xhosa. At the same time, it reveals the reasons why vP is precluded from being elided in these two languages. In Mandarin vP moves to [Spec, AspPi] to check the uninterpretable [asp] feature and in Xhosa vP moves to [Spec, FocP] to realize the focus; consequently, vP may not move to [Spec, EP] for ellipsis.
Keywords: Grammar, Comparative and general -- Ellipsis; Chinese lanaguage -- Ellipsis; Chinese lanaguage -- Grammar, Comparative -- Xhosa; Xhosa lanaguage -- Ellipsis; Xhosa lanaguage -- Grammar, Comparative -- Chinese